Drug Alternative Approach Through Comparative Study of Antibacterial Effect of Curcumin and Andrographolide Against Salmonella enterica serovar Typhimurium - Kirani, Elisa Safa; Sari, Shinta Dewi Permata; Kurnia, Achdi; Rahmadi, Agus (Faculty of Medicine and Health Universitas Muhammadiyah Jakarta, 2024)
Background: Salmonella typhimurium is a pathogen that causes gastroenteritis with a broad host range. Several studies reported antimicrobial resistance against S. Typhimurium. The inappropriate use of antibiotics exacerbates the issue of drug resistance. Indonesian natural products, curcumin, a polyphenol derived from turmeric, and andrographolide from Andrographis paniculata, have shown antibacterial activity due to their various health benefits. These natural products are potential candidates for alternative therapy in S. Typhimurium infection to evade antibiotic resistance. Purposes: This study aims to compare the effectiveness of the antibacterial activity of curcumin and andrographolide against S. Typhimurium. Methods: This study design was true experimental. The curcumin (500 μg/mL, 1000 μg/mL, 5000 μg/mL) and andrographolide (10 μg/mL, 100 μg/mL, 1000 μg/mL) were tested for their antibacterial effects against S. Typhimurium using the Kirby-Bauer diffusion method. Chloramphenicol was used as a positive control, and DMSO was used as a negative control. Inhibition zone bacteria with curcumin treatment compared to andrographolide treatment to assess the effectiveness of the antibacterial activity. Results: Various concentrations of curcumin and andrographolide inhibit the growth of S. Typhimurium bacteria. The highest average of S. Typhimurium inhibition zone was 9 mm and 9.67 mm, with doses of 500 μg/mL curcumin and 1000 μg/mL andrographolide. The andrographolide inhibition zone is larger than curcumin at 1000 µg/mL. These findings showed the potential of andrographolide as a natural antibacterial agent against S. Typhimurium. However, chloramphenicol inhibition zone is still highest between andrographolide and curcumin group doses. Conclusion: Andrographolide has a more effective antibacterial effect against S. Typhimurium than curcumin at 1000 µg/mL based on inhibition zone diameter results. However, chloramphenicol is still more effective as an antibacterial agent against S. Typhimurium.